(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
This study concentrated on the creation and description of invasomes loaded with adapalene for improved topical delivery using a Box-Behnken experimental design. Invasomes, flexible vesicular carriers, were formulated with varying concentrations of limonene and ethanol as penetration enhancers and different levels of phosphatidylcholines and sonication time. The formulation parameters were changed to decrease size of vesicle as well as improve efficiency of entrapment (EE). A size of vesicle 96.65 nm, an EE of 73.32%, as well as potential zeta of -42.23 mV were all shown by the optimized formulation (F6). Drug release that is in vitro which studies indicated continued release of adapalene over 12 hours, with enhanced permeation observed with both limonene and ethanol as enhancers. Research on stability at 4°C and 25°C demonstrated good stability, with only slight changes in vesicle size and EE over 3 months. The results suggested that the optimized adapalene-loaded invasomes offered a promising strategy for improving the transdermal delivery and efficacy that is therapeutic of adapalene for treating dermatological disorders.